An Analysis of Teacher Strategies in Teaching English Speaking at SMPN 2 Praya - Putra, Lalu Yoga Dwi; Muhaimi, Lalu; Putera, Lalu Jaswadi; Sahuddin (Program Studi Pendidikan Bahasa Inggris, 2024)
This study delves into the intricacies of English-speaking instruction at SMPN 2 Praya, aiming to scrutinize the strategies employed by teachers in this context. Through a qualitative research approach, the data was gathered from questionnaire and interviews. The findings reveal a variety of strategies utilized by teachers, ranging from communicative activities to technology integration. Additionally, factors influencing the selection and implementation of these strategies are examined. The study contributes to a deeper understanding of effective pedagogical practices in English speaking instruction, offering insights for educators, policymakers, and curriculum developers to enhance the quality of language education in Indonesian secondary schools.